The contribution of organic acid on heterotrophic CO2 flux from tropical peat: a trenching study - Siti Nurzakiah; Atang Sutandi; Gunawan Djajakirana; Untung Sudadi; Supiandi Sabiham (Journal of Degraded and Mining Lands Management, 2021)
Quantification of CO2 flux from peat has been studied with various methods of measurement and data analysis. Several studies have applied regression analysis to assess carbon flux from tropical peatland as a function of groundwater level. Such an analysis simplified the complex nature of peat decomposition, which involved microbial activities. The study was conducted at Buatan Village, Siak Indrapura Regency, Riau Province, Indonesia. Soil sampling was done every month for a year observation, from July 2018 to June 2019. This study aimed to comprehend CO2 production from the respiration of heterotrophic components (Rh-CO2) as a function of soil properties determined by soil pH, N-NH4, N-NO3, available P, exchangeable-K, C-organic acids, and environmental factors that are determined by soil water content, and groundwater level. The study applied trenching experimentation to quantify Rh-CO2 flux by first removing plant roots from the trenching plot. The CO2 flux and groundwater level were measured for five consecutive days each month for a one-year period. Multiple regression analysis was performed to determine the main determinant for the Rh-CO2 flux. The results showed that seasonal fluctuation of Rh-CO2 flux, negatively correlated with available P (p = 0.037), and positively (p = 0.018) with C-substrate as C-organic acids but not with either of the speciated ones as acetic, lactic, citric, malic, nor oxalic acids. More specifically, the C-organic acids were found as the main determinant factor (p = 0.039) affecting the Rh-CO2 flux.